Demographic Determinants of Public Perceptions of Mental Illness in Heterogeneous Communities of Lagos State Nigeria - Bede C, Akpunne; Francis C, Uzonwanne (Advances in Social Sciences Research Journal, 2015)
Social responses to mental illness depend on factors such as the type of disorder, impact on social function, and cultural concepts and presumptions about the illness. Attitudes toward mental illness are different among families, ethnic groups, individuals, cultures, and countries and are often influenced by the cultural and religious teachings. There is a dearth of research on public perceptions of mental illness in heterogeneous Nigerian communities. A cross-sectional design was used. 210 adults randomly selected from six heterogeneous communities responded to perception of mental illness test (PerMIT) (acceptable reliability coefficient (Cronbach Alpha of .74). There was no observed significant difference in gender, age, educational background, and occupation. Significant difference was however observed in religion. The prevailing culture and misguided societal conclusions which stigmatize mental illness has overbearing influence on peoples’ perception and attitude towards mental illness. Educational interventions and public enlightenment campaigns that debunk misconceptions about mental illness as well as encourage contact with affected persons could play a role in reducing stigma among Nigerians.